Production and evaluation of anti-BP26 monoclonal antibodies for the serological detection of animal brucellosis - Guo, Xiaohan; Sun, Mingjun; Guo, Yu; Wu, Yao; Yan, Xin; Liu, Mengda; Li, Jiaqi; Sun, Xiangxiang; Fan, Xiaoxu; Zhang, Haobo; Sun, Shufang; Wang, Jianlong; et al. (Frontiers in Veterinary Science, 2024)
Brucella BP26 proves to be a highly immunogenic antigen with excellent specificity in brucellosis detection. In China, the authorized use of the Bp26 deleted vaccine M5ΔBP26 for preventing small ruminant brucellosis underscores the importance of developing accurate detection methods targeting BP26, particularly for DIVA purposes.Using the traditional mouse hybridoma technique, we successfully obtained twelve monoclonal antibodies (mAbs) targeting BP26. Evaluating these mAbs' efficacy in detecting various animal brucellosis cases via competitive ELISA method, only the E10 mAb exhibited significant efficiency, being inhibited by 100%, 97.62%, and 100% of brucellosis positive sera from cattle, small ruminants, and canines, respectively. The E10-based cELISA outperformed the BP26-based iELISA in accuracy, particularly for cattle and small ruminant brucellosis, with cELISA sensitivity reaching 97.62% compared to iELISA's 64.29% for small ruminants. While maintaining high accuracy in canine brucellosis detection, cELISA showed slightly lower specificity than iELISA.The epitope of mAb E10 was identified in the amino acid sequence QPIYVYPDDKNNLKEPTITGY, suggesting its potential as a diagnostic antigen for brucellosis. In conclusion, the E10-based cELISA presents an effective means of detecting animal brucellosis, particularly significant for DIVA diagnosis in China where the BP26 mutant vaccine is widely used.